THE PROFILE OF PATIENTS WITH SCHIZOPHRENIA WHO ATTEMPTED SUICIDE - Viktor, Isjanovski Mile; Hadjihamza, Kadri; Raleva, Marija Stefan (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
Abstract: Introduction: Suicide is a complex phenomenon, and deliberate act of taking one's own life, associated with numerous and various biological, social and psychological factors. It is an important psychopathological entity and one of the most demanding clinical problems, which psychiatrists face in their everyday practice, especial in schizophrenic patients. According to literature data, the number of suicides of schizophrenic patients has been increasing in recent decades Objectives: The aim of this study was to determinate the profile of patients with schizophrenia who attempted suicide in the Psychiatric hospital Skopje-Skopje, R.Macedonia. Methods: The study included 114 patients with schizophrenia, 47.4% (n=54) of them attempted suicide, 52.6 %( 60) was group consists of patients with schizophrenia who is not registered for suicide attempt, nor the existence of suicide idea. Psychiatric diagnosis of schizophrenia was based on ICD-10 criteria. Results: Based on the investigation of patients with schizophrenia who attempted suicide, we obtained a typical profile as follows: middle-aged person(31.4 average years), single (61,1% were not married, 44.4% live alone), (79.5%) unemployed, repeatedly hospitalized and history of suicide attempts, attempting suicide using a violent method (poisoning -55.5%, drowing-7.4%, hanging-9.2%, slashing their wrists-16.6%, jumped from height-5.5% etc.) after more than tree weeks of hospital treatment and out of hospital.